2019
DOI: 10.1155/2019/5175949
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of Chest Wall Mobility and Its Correlation with Lung Functions in Healthy Nonsmokers, Healthy Smokers, and Patients with COPD

Abstract: Chest wall circumference measurements are common evaluation methods in clinical settings by therapists in order to obtain chest wall mobility. Previous published results have been conflicting, and there is a lot of variability in the method of testing, which needs testing in different conditions. Seventy subjects (25 healthy nonsmokers, 25 healthy smokers, and 20 COPD) aged between 18 and 70 years participated in the study. Upper and lower chest expansion (CE) measurements (2 levels) are performed with cloth i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
1
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 29 publications
0
38
1
4
Order By: Relevance
“…20 Reddy et al also found very strong correlation of CE at upper thoracic level with FVC (r=0.678, p<0.001) and FEV 1 (r=0.595, p<0.001) in healthy controls. 13 The correlations in our study were weaker, and significantly strong only for males (FVC and FEV 1 ). In one study in COPD patients, chest wall mobility was found to be highly reliable and associated with inspiratory capacity, yet not found to infer pulmonary function to satisfactory level.…”
Section: Discussioncontrasting
confidence: 67%
See 3 more Smart Citations
“…20 Reddy et al also found very strong correlation of CE at upper thoracic level with FVC (r=0.678, p<0.001) and FEV 1 (r=0.595, p<0.001) in healthy controls. 13 The correlations in our study were weaker, and significantly strong only for males (FVC and FEV 1 ). In one study in COPD patients, chest wall mobility was found to be highly reliable and associated with inspiratory capacity, yet not found to infer pulmonary function to satisfactory level.…”
Section: Discussioncontrasting
confidence: 67%
“…The mean CE is lower in patients of ankylosing spondylitis (3.05±1.63 cms) 20 and chronic obstructive pulmonary disease (3.7±0.8 cms). 13,14 Fisher et al found a very strong correlation (r= 0.71, p<0.001) between CE and VC in the patients with ankylosing spondylitis. 20 Reddy et al also found very strong correlation of CE at upper thoracic level with FVC (r=0.678, p<0.001) and FEV 1 (r=0.595, p<0.001) in healthy controls.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Chest expansion was measured in centimeters at the level of the axilla and the xiphisternum using a tape. Each measurement was obtained after maximal expiration followed by maximum inspiration [ 39 , 40 ]. The 6MWD was calculated according to American Thoracic Society guidelines.…”
Section: Methodsmentioning
confidence: 99%